2022
DOI: 10.3389/fphar.2021.775514
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Inhibits FOXM1 Dependent Transcriptional Regulation of POLE2 and Interferes With the Survival of Lung Adenocarcinoma

Abstract: Background: Berberine is one of the most interesting and promising natural anticancer drugs. POLE2 is involved in many cellular functions such as DNA replication and is highly expressed in a variety of cancers. However, the specific molecular mechanism of berberine interfering with POLE2 expression in lung adenocarcinoma (LUAD) is still unknown to a great extent.Method: The KEGG database (Release 91.0) and Gene Ontology (GO) category database were used for functional annotation of differentially expressed gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[46] Berberine can effectively inhibit the proliferation and migration of LUAD. [47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Berberine can effectively inhibit the proliferation and migration of LUAD. [47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle. Palmatine is a class of isoquinoline alkaloids with highly effective biological activity and good water solubility and has shown a good effect in promoting apoptosis of adenocarcinoma cells in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the in vivo studies with Lewis lung carcinoma (LLC) cells in a transplanted tumor mouse model showed that in comparison to the control untreated group, Berberine treatment resulted in significantly higher tumor necrosis alongside a reduction in the expression levels of RRM1 , RRM2 , LIG1 , and POLE2 [ 102 ]. In continuation of the study, Ni et al analyzed the differential expression of genes in Berberine-treated A549 cells and in the lung adenocarcinoma cohort created by the Cancer Genome Atlas (TCGA) and suggested that Berberine interferes with tumor cell proliferation and progression primarily by downregulating the cell cycle and DNA replication related genes [ 92 ]. An overall suppression in the expression of mini-chromosome maintenance complex component 4 (MCM4 ), DNA polymerase alpha subunit 2 (POLA2 ), POLE2 , and DNA primase subunit 1 (PRIM1) in A549 cells treated with Berberine, which are involved in G1/S cell cycle transition and DNA replication, was observed.…”
Section: Potential Therapeutic Effects Of Berberine On Lung Cancermentioning
confidence: 99%
“…An overall suppression in the expression of mini-chromosome maintenance complex component 4 (MCM4 ), DNA polymerase alpha subunit 2 (POLA2 ), POLE2 , and DNA primase subunit 1 (PRIM1) in A549 cells treated with Berberine, which are involved in G1/S cell cycle transition and DNA replication, was observed. Thus, as a mechanism, both in vitro and in vivo lung adenocarcinoma xenografts studies indicated Berberine-mediated downregulation of forkhead box protein M1 (FoxM1), an oncoprotein transcription factor, majorly inhibiting the POLE2 expression involved in DNA replication and affecting the overall survival of lung adenocarcinoma [ 92 ].…”
Section: Potential Therapeutic Effects Of Berberine On Lung Cancermentioning
confidence: 99%
“…Recently, network pharmacology and bioinformatics analysis have provided new ideas and solutions for the study of the mechanism for natural products (Wang et al 2021;Ni et al 2022). Bioinformatics analysis based on proteomics has been widely used to identify differential proteins after cancer chemotherapy (Niu et al 2020;Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%